100 деревянных домов: жилые и садовые домики / И. П. Кожевников, А. П. Шумов - Кожевников Игорь Петрович (Экология, 1993)
Экземпляры: ЧЗ (20151021) / Инвентарный номер: 31440 / Цена: 600 / Сис.шифр: 38 / Авт.знак: К 58 / ББК: 38.55